Рефлексивні функції дипломатичної служби у сучасному суспільстві - Михайлов, Ю. (ХНУРЕ, 2023)
The article examines the peculiarities of the functioning of modern diplomatic services in the world of reflexive analysis. It is proven that diplomatic activity is a reflexive communication and information process, which is carried out by a system of specialized bodies for the performance of political tasks in the international sphere. In the modern information society, diplomats turn into diplomatic agents, whose activities consist of reflection of different interests and cultures, search for compromise positions and certain mutually acceptable actions.